1992
DOI: 10.1210/en.130.2.882
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone-releasing hormone and neuropeptide Y influence deoxyribonucleic acid replication in three anterior pituitary cell types. Evidence for mediation by growth factors released from gonadotrophs

Abstract: Treatment of anterior pituitary reaggregate cell cultures from 14-day-old female rats with physiological doses of the gonadotropin-releasing hormone LHRH or neuropeptide Y (NPY) for 40 h dose-dependently increased [3H]thymidine ([3H]T) incorporation into DNA of cells expressing PRL immunoreactivity (PRL-ir) and of those expressing ACTH-ir, whereas these peptides decreased the number of [3H]T-labeled cells expressing GH-ir. The effects of NPY were of the same magnitude as those of LHRH. The effects of LHRH were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Several candidate peptides can be put forward. Tilemans et al (41) showed that the development of prolactin-, growth-hormone-and ACTH-containing cells in the anterior pituitary of the rat is modulated by luteinizing hormone-releasing hormone and that the action of this hormone is mediated by speci®c growth factors released from gonadotropes. These speci®c growth factors were not identi®ed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate peptides can be put forward. Tilemans et al (41) showed that the development of prolactin-, growth-hormone-and ACTH-containing cells in the anterior pituitary of the rat is modulated by luteinizing hormone-releasing hormone and that the action of this hormone is mediated by speci®c growth factors released from gonadotropes. These speci®c growth factors were not identi®ed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Insight into FS cell function had a new launch when, about two decades ago, Denef and co-workers identified FS cells as cells endowed with paracrine regulatory activities. During the search for a paracrine factor involved in lactotrope -gonadotrope communication (48,49), a factor was unexpectedly detected that caused the attenuation of secretion responses to either stimulatory (24) or inhibitory hormones (25) (see Table 1). This attenuating effect was more pronounced in cell aggregates obtained from low-density gradient fractions, in which FS cells (i.e.…”
Section: Fs Cells In Paracrine Communication In the Anterior Pituitarymentioning
confidence: 99%
“…After 5 days in culture, aggregates were treated with rat IFN-␥ (500 U/ml) (courtesy of Prof. P. Van der Meide; ITRI, Rijswijk, Nederland) for 24 hr. Subsequently, they were fixed in Zamboni fluid (4% paraformaldehyde and 15% saturated picric acid solution in 0.1 M phosphate buffer, pH 7.4) for 4 hr, paraffin-embedded, and sectioned as previously described (Tilemans et al 1992;Denef et al 1989).…”
Section: Immunocytochemistry Of Paraffin-embedded Sections From Rat Amentioning
confidence: 99%
“…Immunostaining was performed as reported previously (Tilemans et al 1992;Denef et al 1989). Briefly, permeabilisation by trypsin (0.1% bovine pancreatic trypsin, Type III; Sigma Chemical, St Louis, MO) and incubation with preimmune swine serum (Dako) (1:5 in PBS, pH 7.4) was followed by overnight reaction with the polyclonal rabbit anti-iNOS antiserum (at a dilution of 1:2000 in PBS).…”
Section: Immunocytochemistry Of Paraffin-embedded Sections From Rat Amentioning
confidence: 99%